Simultaneous estimation of Cefpodoxime proxetil and Ofloxacin In tablet dosage form using RP-HPLC - Annadi Chiranjeevi and Medidi Srinivas (Journal of Applied Pharmaceutical Science, 2014)
A simple, rapid and precise reverse phase liquid chromatographic (RP-HPLC) method was developed and subsequently validated for simultaneous estimation of Cefpodoxime proxetil and Ofloxacin in combined fixed dose oral formulation. The analysis was carried out using X-terra C8 (4.6 x 250mm, 5µm, Make: ACE), pre-packed column. The separation was carried out using a mobile phase containing a 0.25%v/v triethyl amine buffer of pH 3.5 and acetonitrile (30:70 v/v), was pumped at a flow rate of 1.2 ml/min with UV-detector and PDA detection at 227 nm. Both the drugs were well resolved on the stationary phase and the retention times were around 2.747 minute for Cefpodoxime proxetil and 2.076 minute for Ofloxacin. The method was validated and shown to be linear for Cefpodoxime proxetil and Ofloxacin. The correlation coefficients for Cefpodoxime proxetil and Ofloxacin are 0.998 and 0.999 respectively. The relative standard deviations for five replicate measurements in two sets of each drug in the tablets is always less than 2% and mean % error of active recovery not more than ±1.5%. The method was validated for precision and accuracy. The developed method could be applied for routine analysis of Cefpodoxime proxetil and Ofloxacin in tablet dosage form without any interference of excipients.
Keywords: Cefpodoxime proxetil, Ofloxacin, RP-HPLC method development and Validation.